Achieving true flexible machining. (Manufacturing Engineering)
Most machining cells are purchased because of their promise of a high degree of flexibility. But while the potential for a great deal of flexibility is available, very little flexibility is actually achieved. For many, maintaining quality is more important than maximizing flexibility. With the right approach, however, flexibility can be achieved without negatively influencing the quality plan and/or output.